2012
DOI: 10.1038/cddis.2012.127
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the aryl hydrocarbon receptor sensitises human keratinocytes for CD95L- and TRAIL-induced apoptosis

Abstract: In this study, we have analysed the apoptotic effects of the ubiquitous environmental toxin benzo[a]pyrene (BP) in HaCaT cells and human keratinocytes. Although prolonged exposure to BP was not cytotoxic on its own, a strong enhancement of CD95 (Fas)-mediated apoptosis was observed with BP at concentrations activating the aryl hydrocarbon receptor (AhR). Importantly, the ultimately mutagenic BP-metabolite, that is, (+)-anti-BP-7,8-diol-9,10-epoxide (BPDE), failed to enhance CD95-mediated cell death, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
3
16
1
Order By: Relevance
“…A comparable mechanism of xenobiotic‐induced sensitization toward Fas‐mediated apoptosis was observed earlier for benzo[ a ]pyrene in HaCaT cells . Stolpmann et al showed the induction of Fas‐mediated apoptosis by benzo[ a ]pyrene at concentrations activating the aryl hydrocarbon receptor .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A comparable mechanism of xenobiotic‐induced sensitization toward Fas‐mediated apoptosis was observed earlier for benzo[ a ]pyrene in HaCaT cells . Stolpmann et al showed the induction of Fas‐mediated apoptosis by benzo[ a ]pyrene at concentrations activating the aryl hydrocarbon receptor .…”
Section: Discussionsupporting
confidence: 62%
“…A comparable mechanism of xenobiotic‐induced sensitization toward Fas‐mediated apoptosis was observed earlier for benzo[ a ]pyrene in HaCaT cells . Stolpmann et al showed the induction of Fas‐mediated apoptosis by benzo[ a ]pyrene at concentrations activating the aryl hydrocarbon receptor . Furthermore, the phenomenon of sensitization toward Fas‐mediated apoptosis was observed in different carcinoma cell lines after treatment with anticancer drugs like cisplatin and doxorubicin .…”
Section: Discussionsupporting
confidence: 58%
“…46 However, other in vitro reports showed that exposure to BaP or its DNA-reactive metabolite anti-benzo[a]pyrene-7,8-diol-9,10-epoxide (BPDE) induces or sensitizes human cells to either receptormediated or mitochondrial-mediated apoptosis. 47,48 Similar results were obtained using a reverse phase protein array comparing mouse primary liver tumours induced by BaP to their normal adjacent tissues. 49 The results showed both downregulation (eg cleaved caspase 7, caspase 3) and upregulation (Bax, Bad and Bcl-xL) of some pro-apoptotic proteins in tumour tissues.…”
Section: Hallmark 3: Resisting Cell Deathsupporting
confidence: 55%
“…Besides, B[a]P has been found to sensitize human keratinocytes for the apoptosis induced by the Fas ligand or the cytokine TRAIL via an AhR-dependent potentiation of caspase-8 activity [101]. With respect to the B[a]P-induced necrosis/necroptosis, in addition to a possible involvement of some Bcl-2 family members [90,91], it has been shown that ROS production and lipid peroxidation [95] as well as PARP-1, an enzyme involved in DNA repair [94], would also play a role.…”
Section: Pro-and Anti-apoptotic Signalsmentioning
confidence: 99%